2012
DOI: 10.3109/09638288.2012.704123
|View full text |Cite
|
Sign up to set email alerts
|

How policy on employee involvement in work reintegration can yield its opposite: employee experiences in a Canadian setting

Abstract: • It is not that employees are not able to think along or decide on their reintegration trajectory but rather they are expected to do so at times when they cannot oversee their illness and/or recovery trajectory. • Settings out reintegration procedures that are inflexible in practice do not recognize that employee involvement in work reintegration trajectories can develop over time. • The disability management professional has a central role in organizing and supporting employee involvement in work reintegrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…When compared to the findings of an earlier study on workers' experiences with and perceptions on the same RTW policy [11] striking similarities were found. These authors demonstrated with empirical research how policies for involvement, in this Canadian setting of work re-integration, were not as effective as intended, and excluding consequences of these policies.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…When compared to the findings of an earlier study on workers' experiences with and perceptions on the same RTW policy [11] striking similarities were found. These authors demonstrated with empirical research how policies for involvement, in this Canadian setting of work re-integration, were not as effective as intended, and excluding consequences of these policies.…”
Section: Discussionsupporting
confidence: 53%
“…New policies were developed to support early RTW of workers with incapacities (the inability to work due to sickness or injury). These particular strategies do, however, not always have the expected results from the perspectives of re-integrating workers with incapacities in Canada [6][7][8][9][10][11]. Workers' disappointment with early RTW policy is also found in other countries [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much more, the authors suggest that there is a general feeling among those managers that were evaluated, for feeling unheard, frustrated and under pressure when dealing with policies and policy execution. In their opinion this situation led to a low involvement in RTW issues and a weak communication with the stakeholders (Maiwald et al 2013). At the same time, in an Australian organizational setting, McKay, Knott and Delfabbro (2013) found also there is a lack of knowledge among managers concerning the procedures and attitudes imposed by RTW and cancer patients.…”
Section: General Debate Upon Variables Cancer and Rtwmentioning
confidence: 99%
“…employer if possible with the lowest cost to the claim;(101) an employer-based RTW coordinator's primary role is to facilitate a safe transition back to work following an injury with the goals and financial motivations of the employer being considered;(357) and a supervisor is concerned about managing productivity, budgets of his department, and the safety and wellbeing of all staff. (242,(358)(359)(360). To move away from a siloed approach is dependent on the stakeholders' acknowledging and potentially working towards priorities outside of their own self-interests, which, as workers in our study stated, mostly did not occur.…”
mentioning
confidence: 76%